The Protective Effect of Isolation Piles on Deformation of Adjacent Existing Railways - Ying Yang; Shangyong Chen; Jian Li; Shanglin Qin; Chi Liu; Pan Liu (Advances in Civil Engineering)
The isolation pile is the main measure used to reduce the mutual influence between neighboring projects in engineering. In response to the issue of the protective effect of isolation pile technology on the deformation of adjacent existing railway subgrades, this research adopted numerical simulation and a loading deformation analysis method considering the prevailing stress field to study the deformation of existing subgrades and the stress deformation of isolation piles under different lengths of isolation piles. The influence of isolation piles on the deformation of adjacent existing railway subgrades was revealed, and the protective mechanism of isolation piles was analyzed. Based on this, design suggestions and improvement directions for isolation piles in adjacent existing railway engineering were summarized. The main conclusion is that: (1) the length ratio of isolation piles to reinforced piles in new construction projects needs to exceed 2.0 to mitigate uneven settlement of the foundation, resist horizontal compression deformation of the foundation soil, and thereby reduce deformation of the existing subgrade; (2) after the bottom of the isolation pile enters the rock, its own settlement is significantly alleviated, reducing the effects of foundation settlement on the adjacent existing subgrade in new construction projects. When conditions permit, the isolation pile should penetrate deep into the rock layer; and (3) it is possible to consider combining other inexpensive and soil-squeezing piles to form a joint isolation and protective measure, which can save money and further, reduce the deformation of the existing subgrade.